Antibacterial Activity of n-Hexane, Ethyl Acetate, and Ethanol Extracts of Kepundung Seeds (Baccaurea racemosa Mull.Arg.) Against Escherichia coli and Staphylococcus aureus: A Comparative Study with Phytochemical Profiling - Nilsya Febrika Zebua; Syarifah Nadia; Ika Julianti Tambunan; Marcella Maran Gabean; Imanuel Damanik (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
Background: Bacterial infections remain a major global health burden, with antibiotic resistance increasingly limiting treatment options. Natural plant-based compounds represent a promising alternative source of antimicrobial agents. Baccaurea racemosa Mull.Arg. (kepundung), a tropical fruit plant native to Southeast Asia, is traditionally used in folk medicine; however, its seed fractions have not been comprehensively evaluated for antibacterial activity against both Gram-negative and Gram-positive pathogens in a single systematic study. Objectives: This study aimed to characterize the secondary metabolite profile and evaluate the comparative antibacterial activity of n-hexane, ethyl acetate, and ethanol extracts of B. racemosa seeds against Escherichia coli ATCC 25922 and Staphylococcus aureus ATCC 25923. Methods: Seeds were subjected to successive maceration using solvents of increasing polarity (n-hexane, ethyl acetate, ethanol). Phytochemical screening was performed using standard colorimetric assays. Antibacterial activity was assessed by the Kirby–Bauer disk diffusion method at concentrations of 25, 50, 100, and 200 mg/mL, with chloramphenicol as positive control and 1% DMSO as negative control. Results: Phytochemical screening detected alkaloids, flavonoids, tannins, glycosides, saponins, and steroids in all extracts. Against E. coli, the ethanol extract exhibited the largest inhibition zone (44.5 ± 1.7 mm at 200 mg/mL), classified as very strong (>20 mm), compared to ethyl acetate (8.25 ± 3.4 mm) and n-hexane (6.36 ± 1.9 mm). Against S. aureus, the ethanol extract produced an inhibition zone of 13.68 ± 0.33 mm, followed by ethyl acetate (7.46 ± 4.7 mm) and n-hexane (5.08 ± 0.78 mm). The ethanol extract demonstrated significantly higher activity against E. coli than S. aureus (p < 0.05), while n-hexane and ethyl acetate fractions showed comparable moderate activity against both bacteria. Conclusion: Baccaurea racemosa seed ethanol extract demonstrates significant antibacterial activity, particularly against Gram-negative E. coli, attributed to its polar phenolic compounds including flavonoids and tannins. These findings support the potential of B. racemosa seeds as a source of natural antibacterial agents for further pharmaceutical development.